Adoção de práticas de manejo da agrobiodiversidade e estratégias de diversificação dos meios de vida das comunidades rurais em Pirenópolis - Goiás - Mutadiua, Celso Américo Pedro (Universidade Federal de São Carlos, 2012)
The agroecological principles applied on agrobiodiversity management have been seen as a strategic tool for sustainability in agro-ecosystems for rehabilitation of socioeconomic and environmental conditions and for food security purposes. The present research analyzes the adoption of these basic recommended practices on the agrobiodiversity management, considering livelihood strategies. For this purpose are analyzed twelve agricultural establishments, six under the PAIS (Integrated and Sustainable Agroecologic Program) and six out of the PAIS. In this context are identified by a hand, the strategies by which rural families opt for a set of agricultural activities, non-agricultural and social support capabilities to sustain themselves and survive the risks and environmental crises. On the other hand gives to know the main agroecological practices in use in the establishments and the bottlenecks in the process of adoption of agroecological transition. The results shows a positive correlation between the numbers of practices adopted based on agroecologic principles and the number of alternative income generating sources for the farmers.
Adoption of management practices of agrobiodiversity and livelihoods diversification strategies of rural communities in pirenópolis - Goiás
Keywords: Agroecologia; Agrobiodiversidade; Práticas de manejo; Meios de vida; Pluriatividade; Agrobiodiversity; Management practices; Livelihoods; Pluriactivity; CIENCIAS AGRARIAS